Infection with Toxoplasma gondii triggers coagulation at the blood-brain barrier and a reduction in cerebral blood flow - Evelyn M. Hoover; Christine A. Schneider; Christian Crouzet; Tatiane S. Lima; Dario X. Figueroa Velez; Cuong J. Tran; Dritan Agalliu; Sunil P. Gandhi; Bernard Choi; Melissa B. Lodoen (Journal of Neuroinflammation)
Abstract Background Immunothrombosis is the process by which the coagulation cascade interacts with the innate immune system to control infection. However, the formation of clots within the brain vasculature can be detrimental to the host. Recent work has demonstrated that Toxoplasma gondii infects and lyses central nervous system (CNS) endothelial cells that form the blood-brain barrier (BBB). However, little is known about the effect of T. gondii infection on the BBB and the functional consequences of infection on cerebral blood flow (CBF) during the different stages of infection. Main body We demonstrate that brain endothelial cells upregulate the adhesion molecules ICAM-1 and VCAM-1 and become morphologically more tortuous during acute T. gondii infection of mice. Longitudinal two-photon imaging of cerebral blood vessels during infection in mice revealed vascular occlusion in the brain, prompting an analysis of the coagulation cascade. We detected platelet-fibrin clots within the cerebral vasculature during acute infection. Analysis of CBF using longitudinal laser-speckle imaging during T. gondii infection demonstrated that CBF decreased during acute infection, recovered during stable chronic infection, and decreased again during reactivation of the infection induced by IFN-γ depletion. Finally, we demonstrate that treatment of mice with a low-molecular-weight heparin, an anticoagulant, during infection partially rescued CBF in T. gondii-infected mice without affecting parasite burden. Conclusions Our data provide insight into the host-pathogen interactions of a CNS parasite within the brain vasculature and suggest that thrombosis and changes in cerebral hemodynamics may be an unappreciated aspect of infection with T. gondii.